THE EFFECT OF DIFFERENT TYPES OF WEEDS LIVING BY CONTROLLED ON THE GROWTH OF CORN (Zea mays L.) - Nurmiati Nurmiati (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2018)
Weed is one of the plants that cause losses because hold a rivalry or competition with the main plant in absorbing nutrients and water from the soil, and the reception of sunlight for photosynthesis. This study aimed to determine the effect of weed species that live in a controlled manner to the growth corn (Zea mays L.) and determine the factors that affect competition. The type of this research is experiment using completely randomized design (CRD), with three replications and 4 treatments. Weed species is derived from some plants, namely: grass (Cyperus rotundus L.), purslane (Portulaca oleracea L.), Kenamplokan (Physalis angulata L.). Data were analyzed by analysis of variance and to know the real difference was followed by test LSD (Least Significant Difference) with significance level of 5%. Results from the study indicate that there was an influence on the growth of weeds Maize (Zea mays L.) plant height parameter where Fh ≥ Ft (8.96 ≥ 4:26), number of leaves (63.33 ≥ 4:26), leaf width (31.25 ≥ 4:26), dry weight (80 ≥ 4:26), wet weight (7:57 ≥ 4:10) but no effect on the weed species in leaf length parameter wich Fh <Ft (2:06 <4:26).